Strategies for dealing with a mother who is struggling with leukemia – a case study over a three-year period - Czechowicz-Drewniak, Iwona Kinga; Janusz, Bernadetta; Bętkowska-Korpała, Barbara (Psychoonkologia, 2016)
In the case under analysis the authors want to underline the relationship between motherhood (separation distress, longing for physical proximity) and undergoing through an illness (adaptation strategies). The adapted time-span of three years has given the possibility of observing the process of adaptation to the changed rhythm of life resulting from limitations connected with an illness and building up resources that are crucial in the treatment process in connection with attachment patterns. The presented case is built by qualitative thematic analysis and clinical case study in the context of two interrelated processes – adaptation to the motherhood and coping with an oncological illness.